Pregnant women with HIV, vertical transmission of HIV and AIDS cases in children in the state of Sergipe in the years 2010 to 2020: An epidemiological analysis - Xavier, Ketlen Natany Goes (2022)
From the first recorded cases of HIV infection to the present day, about 40 years have passed, enough time for HIV/AIDS to have become a worldwide epidemic, decimating - even if indirectly - several lives. Vertical transmission of HIV is responsible for more than 95% of HIV cases in children, being the most important means of transmission in this age group. This work is a retrospective analytical epidemiological study, based on data from SINAN, SISCEL, SICLOM and SIM. Its objective is to analyze the number of pregnant women living with HIV, the number of children aged 2 to 8 years with HIV and the cases of AIDS in children aged 0 to 8 years according to race and sex. The analysis is restricted to the state of Sergipe and covers the years 2010 to 2020. At the end of the study, it was concluded that there was an abrupt drop in the number of infected pregnant women and in the number of children aged 0 to 8 years with HIV between 2019 and 2020. It was also observed that in 2020 and 2021, of the 57 pregnant women with detectable CV-HIV, only 12 had a viral load between 50-1000 copies/ml. It was observed that AIDS cases in children aged 0 to 8 years have been progressively decreasing and that they are more prevalent in brown girls and under 2 years old.